Tuberous sclerosis complex: Role of radiology as an invaluable tool in management and follow-up - Sharma, Shashi; Sharma, Sandeep; Ramchandran, Priya; Sharma, B B (Indian Journal of Child Health, 2014)
Tuberous sclerosis complex is a genetic disorder, which affects many organs in the body manifesting spectrum of symptomatology. The severity of the disease can be gauged from the extent of involvement of a particular system. Since the disease runs a long course from its presentation at childhood till adulthood and hence the monitoring is very important to have some qualitative life. Other than the common symptomatology and a few laboratory tests, radiological investigations viz. ultrasound, color Doppler sonography, computedtomography and magnetic resonance imaging play a major role in follow-up for the management map road and associated complications. We present a case where a female child had a follow-up from the age of 8 years till 20 years of age. The follow-up and the management were designed mainly as per the radiological findings. The radiological findings have indicated the time for the patient to undergo surgical intervention in addition to the ongoing medical management.